2018
DOI: 10.3390/membranes8030071
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Polyvinylidene Fluoride Membranes with Tailored Properties via Vapour/Non-Solvent Induced Phase Separation

Abstract: The present investigation reports as it is possible to prepared polyvinylidene fluoride (PVDF) membranes for microfiltration (MF) and ultrafiltration (UF) applications, by using triethyl phosphate (TEP) as non–toxic solvent in accordance with the Green Chemistry. Casting solutions containing different concentrations of polyethylene glycol (PEG) were prepared in order to study its effect on the final membrane morphology and properties. The possibility to finely modulate membrane properties was also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…Furthermore, the increasing trend of the membrane pore size can be explained by the effect of slow non-solvent penetration processes due to the phenomenon of solid–liquid demixing during the exposure to humid air through the VIPS. As reported by Marino et al [ 32 ], in the VIPS process, nucleation plays a crucial role in the polymer-lean phase as well as contributing to the formation of highly porous membrane. Therefore, it is recognized that through the polymer chains, an increase in solution viscosity eventually limits water passage, as well as the formation of spongy matrix and a more porous top surface, thus leading to the formation of pores of a larger mean size.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the increasing trend of the membrane pore size can be explained by the effect of slow non-solvent penetration processes due to the phenomenon of solid–liquid demixing during the exposure to humid air through the VIPS. As reported by Marino et al [ 32 ], in the VIPS process, nucleation plays a crucial role in the polymer-lean phase as well as contributing to the formation of highly porous membrane. Therefore, it is recognized that through the polymer chains, an increase in solution viscosity eventually limits water passage, as well as the formation of spongy matrix and a more porous top surface, thus leading to the formation of pores of a larger mean size.…”
Section: Resultsmentioning
confidence: 86%
“…The morphologies of the VIPS membranes portray drastic changes from asymmetric to symmetric as the exposure time was extended. In the VIPS process, the non-solvent vapour present in the humid air gradually interacted with the dope solution during the exposure time before being immersed in the water bath [ 32 ]. It is worth mentioning that vapour often slowly penetrates into the wet film as the wet film is exposed to the water vapour, where the phase separation is induced through formation of the polymer-rich and polymer-lean phase on the top of the cast film.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the Thermal-Induced Phase Inversion (TIPS) and Non-Solvent-Induced Phase Inversion (NIPS) techniques enables the preparation of a membrane fabrication with a desired morphology [ 26 ]. Comparing the TIPS and NIPS techniques, it should be emphasized that the use of TIPS allows for obtaining membranes with better parameters, especially in the field of permeation performances, mechanical strength, and pore size distribution [ 27 , 28 ].…”
Section: Membranes—structure and Propertiesmentioning
confidence: 99%
“…Generally, the electrospinning process produces nanofiber membranes with high porosity and uniform pore size with interconnected pores [51]. With respect to PVDF flat membranes fabricated by phase inversion (porosity around 80%) [51,52], in fact, the porosity of the developed ENMs membranes was higher than 90%, except for the membrane M2 (porosity of 74% ± 1%). Regarding the pore size, it was found that by increasing the polymer concentration (from M4 to M6) the pore size also increased (from 0.87 µm to 1.03 µm).…”
Section: Porosity Pore Size Thickness Contact Angle and Afm Of Enmsmentioning
confidence: 99%